AC electric field-assisted fabrication of ice-templated alumina materials and remarkable enhancement of compressive strength. (1st January 2022) - Akurati, Sashanka; Qian, Shizhi; Ghosh, Dipankar
Abstract: A novel methodology was developed that uniquely employs alternating current (AC) electric field to fabricate ice-templated ceramics. In the methodology, AC field was applied to an aqueous ceramic suspension, and then ice-templating was performed. Field application to an aqueous ceramic suspension resulted in a net motion of ceramic particles due to DC voltage generation. Suspension concentration increased near one of the electrodes, which was controllable through AC frequency and field duration. Density of the very bottommost regions in sintered materials increased with field duration, attributed to increased local suspension concentration. In sintered materials, the thickness of non-templated region increased with field duration, whereas templated microstructure turned increasingly dendritic with field duration, suggesting a strong influence of AC field on the growth characteristics of ice crystals. AC-field assisted materials exhibited remarkably enhanced compressive strength without any change in porosity. This work contributes to advancing the ice-templating technology using externally energized fields. Graphical Abstract: Image, graphical abstract